2016
DOI: 10.1242/bio.018226
|View full text |Cite
|
Sign up to set email alerts
|

A genetically encoded biosensor for visualizing hypoxia responsesin vivo

Abstract: Cells experience different oxygen concentrations depending on location, organismal developmental stage, and physiological or pathological conditions. Responses to reduced oxygen levels (hypoxia) rely on the conserved hypoxia-inducible factor 1 (HIF-1). Understanding the developmental and tissue-specific responses to changing oxygen levels has been limited by the lack of adequate tools for monitoring HIF-1 in vivo. To visualise and analyse HIF-1 dynamics in Drosophila, we used a hypoxia biosensor consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 47 publications
(60 reference statements)
3
50
0
Order By: Relevance
“…To understand whether trh 1 /trh 2 mutant cells are under hypoxia, we used the hypoxia biosensor GFP-ODD, in which the GFP is fused to the oxygen-dependent degradation (ODD) domain of Sima, under the control of the ubiquitin-69E ( ubi ) promoter [36]. We first confirmed that GFP-ODD signal was low under normoxia (21% O 2 ) and enhanced under hypoxia (5% O 2 , Fig 2A) in wild-type late-stage embryos when tracheal tubules are already formed and functioning [36]. Indeed, enhanced GFP signal was ubiquitous under hypoxia in wild-type embryos, with some pronounced focal GFP signals (Fig 2A, upper row, and Fig S2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand whether trh 1 /trh 2 mutant cells are under hypoxia, we used the hypoxia biosensor GFP-ODD, in which the GFP is fused to the oxygen-dependent degradation (ODD) domain of Sima, under the control of the ubiquitin-69E ( ubi ) promoter [36]. We first confirmed that GFP-ODD signal was low under normoxia (21% O 2 ) and enhanced under hypoxia (5% O 2 , Fig 2A) in wild-type late-stage embryos when tracheal tubules are already formed and functioning [36]. Indeed, enhanced GFP signal was ubiquitous under hypoxia in wild-type embryos, with some pronounced focal GFP signals (Fig 2A, upper row, and Fig S2C).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, enhanced GFP signal was ubiquitous under hypoxia in wild-type embryos, with some pronounced focal GFP signals (Fig 2A, upper row, and Fig S2C). The signal of mRFP-nls, also under the control of ubi promoter as an internal control, remained constant under hypoxia (Fig 2A, bottom row, and Fig S2D) [36]. Quantification of the GFP/RFP ratio revealed a significant difference between normoxia and hypoxia conditions (Fig 2B).…”
Section: Resultsmentioning
confidence: 99%
“…6A). To confirm the hypoxic state of the fat tissue, we made use of a genetic hypoxia reporter based on a GFP fusion with the oxygendependent degradation (ODD) domain of HIF-1a 58 . Under normoxic conditions, GFP::ODD is ubiquitinylated through the activity of Hph, targeting it for degradation.…”
Section: Loss Of Btl and Reduced O2 Levels Cause Adipose Tissue Hypoxiamentioning
confidence: 99%
“…ΔGbp1,2 14 was kindly given by T. Koyama. Hph Δ9 (Fatiga Δ9 , Fga Δ9 ) was a kind gift of P. Wappner, ubi-ODD::GFP hypoxia sensor 58…”
Section: Fly Strains and Husbandrymentioning
confidence: 99%
See 1 more Smart Citation